2016
DOI: 10.1111/ecc.12603
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life after bone sarcoma surgery around the knee: A long-term follow-up study

Abstract: It remains unclear if quality of life (QoL) improvements could be expected in young patients after malignant bone tumour surgery after 2 years. To assess the course of QoL over time during a long-term follow-up, malignant bone tumour survivors of a previous short-term study were included. Assessments were done at least 5 years patients; 20 patients were included for this study, 10 males; mean age at surgery 15.1 years and mean follow-up 7.2 years. Twenty-one patients of the initial cohort (47%) deceased. Fifte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 42 publications
(61 reference statements)
3
11
0
Order By: Relevance
“…Similar to the current study, categories depicting psychological health and social function were not influenced [6]. Other studies emphasized the trend that was found [8,19]. Both studies investigated QoL in young patients with bone tumors using the SF-36 and observed that QoL is inferior regarding physical health compared to control.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Similar to the current study, categories depicting psychological health and social function were not influenced [6]. Other studies emphasized the trend that was found [8,19]. Both studies investigated QoL in young patients with bone tumors using the SF-36 and observed that QoL is inferior regarding physical health compared to control.…”
Section: Discussionsupporting
confidence: 84%
“…Both studies investigated QoL in young patients with bone tumors using the SF-36 and observed that QoL is inferior regarding physical health compared to control. However, both could not find a psychological influence on QoL [8,19]. However, both these studies included only young patients in their cohorts.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This was, for some, more straightforward due to their personality and/or timely professional and informal support available. But this might also reflect Bekkering’s et al 36 suggestion that similar psychological status of patients with sarcoma and healthy peers found in their study was due to positive emotions felt after completion of treatment and survival, in what was termed the ‘response shift’.…”
Section: Discussionsupporting
confidence: 64%
“…Some of the most pertinent reference values for the first-year postsurgical treatment for patients with mega-prosthesis of the knee are as follows: the possibility of recovering 90 • of knee flexion in 50% of the patients, 3 months after surgery; for quadricep strength recovery in 25% of patients, 12 months after surgery, the values are less than three according to the manual muscle test (0-5) 56 but with the chance of improving motor function even 12-24 months postsurgery. 57,58 Beyond the oncological phases, further assessments are carried out periodically by the physiotherapist to monitor progress. This assessment is done at the beginning and at the end of the rehabilitation process, and also when clinical conditions change.…”
Section: Follow-up Rehabilitative Assessmentmentioning
confidence: 99%